Systematic Analysis of mRNAs and ncRNAs in BMSCs of Senile Osteoporosis Patients - Geng, Yiyun; Chen, Jinfu; Chang, Chongfei; Zhang, Yifen; Duan, Li; Zhu, Weimin; Mou, Lisha; Xiong, Jianyi; Wang, Daping (Frontiers in Genetics, 2021)
Senile osteoporosis (SOP) is a worldwide age-related disease characterized by the loss of bone mass and decrease in bone strength. Bone mesenchymal stem cells (BMSCs) play an important role in the pathology of senile osteoporosis. Abnormal expression and regulation of non-coding RNA (ncRNA) are involved in a variety of human diseases. In the present study, we aimed to identify differentially expressed mRNAs and ncRNAs in senile osteoporosis patient-derived BMSCs via high-throughput transcriptome sequencing in combination with bioinformatics analysis. As a result, 415 mRNAs, 30 lncRNAs, 6 circRNAs and 27 miRNAs were found to be significantly changed in the senile osteoporosis group. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were applied to analyze the function of differentially expressed mRNAs and ncRNAs. The circRNA–miRNA–mRNA regulatory network was constructed using the cytoHubba plugin based on the Cytoscape software. Interestingly, circRNA008876-miR-150-5p-mRNA was the sole predicted circRNA-miRNA-mRNA network. The differential expression profile of this ceRNA network was further verified by qRT-PCR. The biological function of this network was validated by overexpression and knockdown experiments. In conclusion, circRNA008876-miR-150-5p-mRNA could be an important ceRNA network involved in senile osteoporosis, which provides potential biomarkers and therapeutic targets for senile osteoporosis.